Short‐term estimates of phytoplankton growth and mortality in a tidal estuary. (8th August 2018) - Anderson, Sean R.; Diou‐Cass, Quintin P.; Harvey, Elizabeth L.
Abstract: Rates of phytoplankton growth and mortality are poorly defined over short‐time scales (hours to days), despite these scales being relevant over the daily tidal cycle in coastal marine areas. To assess the influence of tidal variability on phytoplankton rates, we performed eight, same‐day dilution experiments at high and low tide (6‐h intervals) in the Skidaway River Estuary, Georgia, measuring phytoplankton growth, microzooplankton grazing, and virus‐induced mortality. Chlorophyll and group‐specific biomass ( Synechococcus spp., picoeukaryotes, and nanoeukaryotes) varied between tides and multidimensional scaling clustering of tidal biomass revealed separation in community composition based on tide. Rates also varied significantly over the tidal cycle, especially microzooplankton grazing, which was higher at low tide in most experiments with rates ranging from 0–3.77 d −1 at low tide to 0–1.51 d −1 at high tide. Virus‐induced mortality rates were rarely detected, only being observed in Synechococcus spp. in three experiments (0.3–0.8 d −1 ) and picoeukaryotes twice (~ 0.36 d −1 ). The differences in grazing and growth rates observed between the two tides were not explained by temperature, salinity, or sunlight (i.e., time of day) and grazing was only weakly explained by initial chlorophyll concentration ( R 2 = 0.36), highlighting the influence of community composition on rate measurements. These results suggest that within tidally influenced areas, short‐term sampling over the tidal cycle is essential to accurately characterize daily phytoplankton dynamics and reliably monitor and predict shifts in primary production and coastal ecosystem health.